Grid Planning Method of Medium Voltage Distribution Network Including Distributed Power Sources based on Timing Characteristics - Zhang, Zhan; Yang, Jin (International Journal of Electric Power and Energy Studies, 2024)
Aiming at the problems of unbalanced load distribution of feeders and low utilization rate of system resources in existing medium voltage(MV) distribution network planning, it is difficult to meet the requirements of future grid construction, Propose a grid planning method of MV distribution network including distributed generator(DG) based on timing characteristics. Firstly, based on the existing grid planning achievements and temporal characteristics analysis, the grid structure and planning strategy of the MV distribution network are formed. Secondly, based on the network planning strategy, establish a dual level planning model for both internal and external distribution networks. The inner model uses comprehensive performance indicators as fitness functions to solve the optimal division of the distribution network grid, while the outer model calculates the distributed power capacity configuration of each grid with the goal of maximizing the consumption of DG. Then, based on the established dual layer planning model for the distribution network, genetic algorithms and self programming algorithms are used to solve the model by interconnecting the internal and external layers. Finally, the practicality and effectiveness of the proposed model and method were verified through practical examples combined with evaluation indicators.